2016
DOI: 10.1002/ijc.30039
|View full text |Cite
|
Sign up to set email alerts
|

From junk to master regulators of invasion: lncRNA functions in migration, EMT and metastasis

Abstract: Metastasis is a multistep process that involves the dissemination of cells from the primary tumor and colonization of distant secondary organs. Epithelial cells at the invasive front of a carcinoma acquire an enhanced migratory phenotype in a process called epithelial-to-mesenchymal transition (EMT). This cellular plasticity seems to drive the initiation of metastasis. Identifying important molecules and understanding their molecular mechanisms is a key to cancer prognosis and the development of therapeutics f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
182
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(187 citation statements)
references
References 155 publications
(219 reference statements)
2
182
0
1
Order By: Relevance
“…Of the thousands of IncRNAs discovered, a few have been shown to play crucial roles in different biological processes through chromatin modification, epigenetic regulation, alternative splicing, and translational control [26, 27]. In particular, a number of IncRNAs are emerging as critical regulators of tumor progression and metastasis [28, 29]. The metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), also known as nuclear-enriched abundant transcript 2 (NEAT2), is a large, ubiquitously expressed IncRNA [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the thousands of IncRNAs discovered, a few have been shown to play crucial roles in different biological processes through chromatin modification, epigenetic regulation, alternative splicing, and translational control [26, 27]. In particular, a number of IncRNAs are emerging as critical regulators of tumor progression and metastasis [28, 29]. The metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), also known as nuclear-enriched abundant transcript 2 (NEAT2), is a large, ubiquitously expressed IncRNA [30].…”
Section: Introductionmentioning
confidence: 99%
“…The metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), also known as nuclear-enriched abundant transcript 2 (NEAT2), is a large, ubiquitously expressed IncRNA [30]. Extensive studies have indicated that MALAT1 plays an oncogenic role in various cancers via multiple mechanisms, including triggering EMT in tumor cells and promoting tumor metastasis [28, 31]. Importantly, MALAT1 has been found to be induced by TGF-β1 and mediate TGF-β1-triggered EMT in retinal pigment epithelial cells [32].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are very abundant with estimates of 430 000 lncRNAs transcripts in the human genome. [71][72][73][74][75][76][77] One group of investigators estimated that there were close to 60 000 lncRNAs including 8000 oncologic lncRNAs. 74 A growing number of these lncRNAs are being isolated and characterized from thyroid and other cancers.…”
Section: Non-coding Rnas and Emt Micrornas And Emtmentioning
confidence: 99%
“…LncRNAs, which are emerging as pivotal regulation factors of cell biological behavior, can alter tumor growth kinetics, Author Manuscript Published OnlineFirst on December 11, 2017; DOI: 10.1158/0008-5472. CAN-17-2356 promote lymphangiogenesis and distant metastasis of cancer by interacting with RNA, DNA, or proteins [14,15]. In recent years, the expression of certain lncRNAs has been frequently reported to be functionally important for cervical cancer, including lincRNA-p21 [16], HOXA11-AS [17], HOTAIR [18] and ANRIL [19].…”
Section: Introductionmentioning
confidence: 99%